THE IMPACT OF CONSUMER ANIMOSITY, CONSUMER ETHNOCENTRISM, AND PRODUCT JUDGMENT ON WILLINGNESS TO BUY GLOBAL FAST-FOOD PRODUCTS - Setiawan, Angie Ivana; Setiobudi, Auditia (Jurnal Manajemen Terapan dan Keuangan, 2026)
This study investigates the influence of two critical affective constructs, Consumer Animosity (CA) and Consumer Ethnocentrism (CE), on product judgment and the willingness to buy international fast-food products within the Indonesian market context. The research is motivated by the increasing prevalence of public sentiment and organized boycott movements, which necessitate a rigorous examination of whether emotional reactions directed toward a product's country of origin translate into tangible changes in consumer purchasing behavior. Utilizing a convenience sampling technique, primary data were collected via an online survey, yielding 385 valid responses from Indonesian consumers. The hypothesized relationships among the four core variables (CA, CE, PJ, and WTB) were subsequently analyzed using the Partial Least Squares (PLS-SEM). Implication from this research, managers must implement robust risk management protocols to decouple brand identity from negative Country of Origin (COO) sentiment, primarily through intensified localization efforts and emphasizing the brand's contribution to the local economy.